Dynamic functional and structural remodeling during retinal regeneration in zebrafish - Lindsey M. Barrett; Diana M. Mitchell; Peter C. Meighan; Michael D. Varnum; Deborah L. Stenkamp (Frontiers in Molecular Neuroscience, 2022)
IntroductionZebrafish regenerate their retinas following damage, resulting in restoration of visual function. Here we evaluate recovery of retinal function through qualitative and quantitative analysis of the electroretinogram (ERG) over time following retinal damage, in correlation to histological features of regenerated retinal tissue.MethodsRetinas of adult zebrafish were lesioned by intravitreal injection of 10 μM (extensive lesion; destroys all neurons) or 2 μM (selective lesion; spares photoreceptors) ouabain. Unlesioned contralateral retinas served as controls. Function of retinal circuitry was analyzed at selected timepoints using ERG recordings from live zebrafish, and whole eyes were processed for histological analyses immediately thereafter.ResultsQualitative and quantitative assessment of waveforms during retinal regeneration revealed dynamic changes that were heterogeneous on an individual level within each sampling time, but still followed common waveform recovery patterns on a per-fish and population-level basis. Early in the regeneration period (13–30 days post injury; DPI), for both lesion types, b-waves were essentially not detected, and unmasked increased apparent amplitudes, implicit times, and half-widths of a-waves (vs. controls). In control recordings, d-waves were not obviously detected, but apparent d-waves (OFF-bipolar responses) from regenerating retinas of several fish became prominent by 30DPI and dominated the post-photoreceptor response (PPR). Beyond 45DPI, b-waves became detectable, and the ratio of apparent d- to b-wave contributions progressively shifted with most, but not all, fish displaying a b-wave dominated PPR. At the latest timepoints (extensive, 90DPI; selective, 80DPI), recordings with measurable b-waves approached a normal waveform (implicit times and half-widths), but amplitudes were not restored to control levels. Histological analyses of the retinas from which ERGs were recorded showed that as regeneration progressed, PKCa + ON-bipolar terminals and parvalbumin + amacrine cell processes became more stereotypically positioned within the deep sublaminae of the INL over recovery time after each lesion type, consistent with the shift in PPR seen in the ERG recordings.DiscussionTaken together, these data suggest that photoreceptor-OFF-bipolar component/connectivity may functionally recover and mature earlier during regeneration compared to the photoreceptor-ON-bipolar component, though the timeframe in which such recovery happens is heterogeneous on a per-fish basis. Collectively our studies suggest gradual restoration of ON-bipolar functional circuitry during retinal regeneration.